2020
DOI: 10.1111/joor.13113
|View full text |Cite
|
Sign up to set email alerts
|

Physical, psychological and socio‐demographic predictors related to patients’ self‐belief of their temporomandibular disorders’ aetiology

Abstract: Background The aetiology of temporomandibular disorders (TMDs) has been widely discussed in literature, but little is known about patients’ self‐belief of their TMD aetiology. Objective For six categories of self‐believed aetiology of the TMD complaint (viz., occlusal factors, physical trauma, emotional stress, deep pain input, parafunctions and unknown), associations with physical, psychological and socio‐demographic predictors were assessed. Methods In this retrospective study, medical records of 328 TMD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…There are some relevant studies that evaluated the beliefs of patients with TMD and other painful conditions. [26][27][28][29][30] Beliefs in causal attributions in which patients express beliefs about the cause of their own conditions are relevant among these studies. For instance, one study investigated whether the existence of an association between self-reported oral waking behaviours and TMD pain depended on patients' beliefs that these behaviours were prejudicial.…”
Section: Temp Oromandibul Ar Disorder S (Mis) B Eliefs and Their Impac Tmentioning
confidence: 99%
“…There are some relevant studies that evaluated the beliefs of patients with TMD and other painful conditions. [26][27][28][29][30] Beliefs in causal attributions in which patients express beliefs about the cause of their own conditions are relevant among these studies. For instance, one study investigated whether the existence of an association between self-reported oral waking behaviours and TMD pain depended on patients' beliefs that these behaviours were prejudicial.…”
Section: Temp Oromandibul Ar Disorder S (Mis) B Eliefs and Their Impac Tmentioning
confidence: 99%
“…Contrary to initial presumptions, occlusal factors play a minor role in the development of TMDs [ 9 ]. Nevertheless, a significant number of patients relate TMD symptoms with occlusal factors and therefore consult a dentist or orthodontist at first when symptoms occur [ 10 ]. According to the current state of art, biological, psychological and social factors are crucial for the pathogenesis of TMD [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…TMDs represents a group of musculoskeletal/neuromuscular conditions that may affect masticatory muscles, the temporomandibular joint (TMJ) and its associated structures [ 6 , 7 ]. The main symptoms and signs of TMD include masticatory pain, headaches, limited mandibular motion and its deviation pattern, TMJ noises, subluxation or/and jaw locked, jaw functional limitations, neck pain and poor sleep quality [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…These components can be considered as initiating, predisposing or perpetuating factors. The most common reasons concern direct and indirect trauma, repetitive microtrauma, systemic and local factors, postural and parafunctional habits, genetic determination as well as psychosocial findings relating to depression and anxiety [ 2 , 6 , 8 , 13 , 15 , 16 , 17 , 18 , 19 ]. The role of occlusion still remains unclear [ 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation